The Linkage between Corporate Board Independence and Firm Performance: Empirical Evidence from the Family Firms in Pakistan1 - MENGYUN, WU; UM-E-HABIBA; ANWAR, MUHAMMAD MUDASSAR; AKBAR, MUHAMMAD IMAD-UD-DIN; HUSNAIN, MUHAMMAD (The journal of contemporary issues in business and government, 2021)
Everywhere around the globe, family companies are a prominent and quite sound identity. Dominant families have a solid motive for extracting personal advantages through minority shareholder resource exploitation and indulging in lessening the shareholders’ wealth, especially in developing countries. An effective governance system guards against these activities while still influencing long-term results by eliminating these. This analysis broadens this focus by exploring the impact of independent directors, board scale, leverage, dividend delivery, and firm size on financial performance in Pakistani listed family-owned businesses. Secondary data from released annual reports and governance practices reports was used to analyze 212 family-owned firms from 2010 to 2017. Throughout this analysis, the static or dynamic models: fixed - effects (FE), random effect (RE), and generalized form of the moment (GMM) are important measurement methods. The findings indicate that board independence positively impacts firm financial efficiency, suggesting that governance is successful in family businesses. In contrast, board size has a negative impact on the performance of a firm, offering ineffective governance. Finally, the study includes governance suggestions for lenders as well as all other stakeholders.